Uneployment Dynamics in Central Europe: A Labour Flow Approach - Flek, Vladislav; Mysíková, Martina (Prague Economic Papers, 2015)
We analyse labour market flows and unemployment rate dynamics in the Czech Republic (CR), Slovakia and Poland. Relative involvement of working-age individuals in movements between various labour market states appears to be approximately five times lower in Central Europe than in the U.S./UK. Compared to neighbouring countries, the CR suffers from a relatively weaker net flow of individuals from unemployment to employment. This net flow alone would cut the unemployment rate in Poland more than twice as fast as in the CR. In particular, currently unemployed Czech men, individuals with primary education, and the 55-65 age group are adversely affected by this national-specific feature of labour market flows.
Keywords: EU-SILC; labour market flows; longitudinal data; unemployment